Choline transport for phospholipid synthesis: An emerging role of choline transporter-like protein 1 - Hedtke, Vera (Exp Biol Med (Maywood), 2019)
This review provides a summary of recent discoveries in choline transport and the proteins mediating it with a specific focus on the choline transporter-like proteins (CTL)/solute carriers 44 A (SLC44A) and their role in phospholipid metabolism. Since its initial cloning, particularly, the CTL1/SLC44A1 transporter has been investigated further and its ubiquitous expression characterized in various cells and tissues of mouse, rat, and human origin. We describe the role of this choline transporter both in the plasma membrane and in the mitochondria and summarize novel aspects of choline transport regulation in the muscle, nervous system, and cancer. IMPACT STATEMENT: This review will provide a summary of recent advances in choline transport research and highlight important novel areas of focus in the field.